Risk Factors Evaluation and Antiviral Eradication Therapies Among HCV Infected Family Members of Northern Regions, Pakistan - Ulllah, Ikram; Ali, Mashhood; Altaf, Hamza; Aziz, Shahid; Ali, Salamat; Mustafa, Ghulam; Akbar, Ali; Jadoon, Muhammad Ayub; Rasheed, Faisal (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Hepatitis C virus (HCV) poses a global health threat, often transmitted intra-familial. This study aims to assess HCV transmission within Pakistani households and identify associated risk factors. To analyze 125 household subjects for HCV infection prevalence, demographics, genotypes, and risk factors. We conducted a comprehensive analysis of 125 household subjects to determine HCV prevalence. Demographics, genotypes, and risk factors were carefully examined through rigorous data collection and statistical analysis. Of the 125 households surveyed, 57 tested positive for HCV, indicating a high prevalence rate. Within these households, 121 individuals were infected, with a slightly higher proportion of females (59.5%). The distribution of infections varied across regions, with Islamabad showing the highest prevalence at 56.14%. Among the infected individuals, offspring were significantly affected (42.1%), followed by spouses (29.8%) and siblings (28%). Genotype 3a emerged as the most prevalent strain. Risk factors contributing to intra-familial transmission included major surgeries, dental procedures, hospitalizations, and blood transfusions. Furthermore, sharing personal items such as blades and towels also posed significant risks. Intra-familial transmission is a key driver of HCV spread within Pakistani households. The study's findings underscore the urgent need for targeted interventions to control and prevent HCV transmission within familial settings. Strategies should focus on raising awareness about risk factors and promoting preventive practices. Additionally, The most effective outcomes in the current study were observed with the combination therapy of Sofosbuvir and Ribavirin, achieving an End of Treatment Response (ETR) of 73% and a Sustained Virologic Response (SVR) of 72%.